Division of Labour in Coastal Community: The Equity of Role-Play Between Bugis Women and Men in Kupang - Syahrul, Syahrul; Zahrawati, Fawziah; Nursaptini, Nursaptini (UIN Sunan Kudus, 2022)
The study aims to know the division of labor between women and men in the Bugis Families at Kupang coastal community. Collecting the data through Focus Group Discussion (FGD) with 20 familial members such as wives and husbands, and gathering in-deep information by conducting interviews and observations. The result of this study shows that: (1) In Bugis families, wife and husband work representing social solidarity because there is no role play that the only wife should cook, clean, and wash, while several husbands stay at home for cooking, washing, and nursing. (2) Gender division of labor approach to highlight the role, benefits, and risks of women and men in the coastal area. Women and men supply seaweed farming as a family business, and both of them work with a division of labor. The wife used the extra money for daily expenses, whereas the husband used their extra money for bigger investments. (3) Both women and men work not only equal but also equity because fishing is dangerous for women, but men can do it, while fishery multi-products are difficult for Bugis men, but it easy for women.